Ludic Social Interaction During Forward Head Posture Therapy Causes More Attendance to Physical Therapy Sessions in Older Adults - Astorga Verdugo, Sebastián (2021)
Objective: This study aimed to compare the attendance to postural reeducation physiotherapeutic treatment sessions with ludic social interaction for the forward head posture in older adults with the attendance to sessions without this ludic social interaction. Material and methods: The study used an experimental, longitudinal design. Eighty-eight participants met the following participation criteria: older adults > 60 years and < 90 years, craniovertebral angle < 50 degrees, and neck pain < 3 VAS. They were randomly divided into two groups: a control group that received a postural reeducation physiotherapeutic treatment for forward head posture without ludic social interaction, and an experimental group that benefited from a postural reeducation physiotherapeutic treatment with ludic social interaction. Both groups were subdivided according to age ranges 60-69, 70-79, and ≧ 80 years. Physiotherapeutic treatment for both groups lasted 4 months, completing 32 sessions (2 weekly sessions). Results: There were statistically significant changes in the comparison of assistance to physiotherapeutic treatment between the two groups (p <0.05). The experimental group presented an average attendance to the treatment of 83% versus the control group that presented an average attendance to the treatment of 76%. There were no statistically significant changes according to the intra-and intergroup age range (p> 0.05). Conclusion: The experimental group that underwent the postural reeducation physiotherapeutic treatment with long-term ludic social interaction showed greater attendance to physiotherapeutic treatment versus the control group without ludic social interaction in older adults with forward head posture. Practical applications: Developing a long-term physiotherapeutic treatment program adding ludic social interaction can have beneficial results in attending physiotherapeutic treatment sessions.